Biological Activities and Possible Dental Application of Three Major Groups of Polyphenols - Hiroshi Sakagami (Elsevier, 2014)
Abstract.: The present article reviewed the biological activities and possible dental application of three major polyphenols, i.e., lignin-carbohydrate complexes, tannins, and flavonoids, citing mostly our in vitro studies together with those from other groups. All these polyphenols showed much lower tumor-selective cytotoxicity against oral squamous cell carcinoma cells vs. normal oral cells (gingival fibroblast, pulp cell, periodontal ligament fibroblast), in comparison to popular chemotherapeutic antitumor drugs. Several compounds showing higher tumor-selectivity did not induce internucleosomal DNA fragmentation, a biochemical hallmark of apoptosis, in oral carcinoma cell lines. Lignin-carbohydrate complex protected the cells from the cytopathic effects of HIV infection and UV irradiation more efficiently than other polyphenols. Limited digestion of lignin-carbohydrate complex suggests that the lignin moiety is involved in the prominent anti-HIV activity, whereas the carbohydrate moiety may function in immunopotentiating activity through a cell surface receptor. Alkaline extract of plant leaf, which contains higher amounts of lignin-carbohydrate complex, showed potent anti-inflammatory action against IL-1β-stimulated human gingival fibroblasts. Local application of lignin-carbohydrate complex through oral mucosa is recommended, considering its poor intestinal absorption. Keywords:: polyphenol, oral carcinoma, gingivitis, viral infection, anti-UV activity